Peningkatan Fungsi Kognitif Lansia Melalui Terapi Mewarnai Gambar Di Panti Sosial Mandalika Nusa Tenggara Barat - Putri Rusiana, Harlina; Rias Pratiwi Safitri; Fitri Romadonika; Baiq Nurul Hidayati; Anna Layla Salfarina (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2024)
Increasing age and increasing prevalence of non-communicable diseases are the main factors causing cognitive function decline, Cognitive function decline will have an impact on decreasing daily social activities in the elderly which will become a quality of life problem and have an impact on financing family maintenance, community and government. This situation can be anticipated with a therapy that can improve cognitive function, one of which is coloring therapy. This therapy is proven to have effectiveness in improving the cognitive function of the elderly. This service was carried out at the Mandalika Social Institution NTB involving 18 elderly people. Coloring therapy was carried out for two days with 4 stages, starting from preparing the room, preparing participants, implementing therapy and evaluation. It was found that the result of a picture of cognitive function after coloring therapy was that 56% of the elderly did not have cognitive impairment. From the results of this service, it is hoped that the NTB Mandalika elderly social institution can apply coloring therapy as a treatment in improving the cognitive function of the elderly and doing other therapies in groups to improve the welfare of the elderly